A Note on Stabilization of Discrete Nonlinear Systems. (15th February 2011) - Tang, Fengjun; Yuan, Rong
Abstract : We deal with the stabilization problem of discrete nonlinear systems. We construct a control Lyapunov function on discrete nonlinear systems. Then, we present a new method to construct a continuous state feedback law.